Analysis of relation between placental lesions and perinatal outcome according to Amsterdam criteria: a comparative study - Loverro, Maria Teresa; Damiani, Gianluca Raffaello; Di Naro, Edoardo; Schonauer, Luca Maria; Laforgia, Nicola; Loverro, Matteo; Capursi, Teresa; Muzzupapa, Giuseppe; Resta, Leonardo (Acta Biomedica Atenei Parmensis, 2020)
Background: To verify the correlation between histological examination of the placenta (HP), classifying the lesions according to the Amsterdam criteria (AC), and the main neonatal pathological patterns. Methods: This prospective study carried out at the University of Bari between May 2015 and May 2017,enrolled 350 pregnant women. Complete obstetric history and HP was collected. 380 newborns were also enrolled. The analysis was also carried out by comparing the incidence of the various placental pathologies in the sample of physiological pregnancies (PP), represented by 142 cases, with the incidence of the group with placental anomalies (PA). The statistical software used was STATA MP11. Results: Respiratory disorders (61 cases) are significantly correlated with generic PA (p=0.006). Neonatal sepsis (15 cases) was significantly correlated with placental inflammation (p=0.035) and villitis of unknown origin (p=0.039).Twin pregnancies (50 cases) were correlated with generic PA (p=0.00001) and late maternal malperfusion (p=0.00001). Congenital cardiopathies (50 cases) were correlated with the villitis of unknown origin and PA (p=0.0000). Preterm birth (145 cases)was correlated with the premature malperfusion (p=0, 0011) and PA (p=0.0000); SGA (low weight in relation to the gestational age - 75 cases) neonates were correlated with the early malperfusion (p=0.00000) and the generic PA (p=0.00000). Conclusions: The present study has therefore verified whether in reality the HP can be of great help to the neonatologist in the nosological and therapeutic setting of the pathological newborn. The pathological examination of the placenta is nevertheless essential to clarify the causes of the stillbirths and that these causes are particularly important for the obstetric and neonatal outcome of subsequent pregnancies.